1980
DOI: 10.1093/nar/8.20.4821
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of promoter selection by the bacteriophage T7 RNA polymerase in vitro

Abstract: During bacteriophage T7 infection a phage-specified RNA polymerase transcribes the late phage genes in two temporal classes (class II and class III). In this report, we show that the purified phage polymerase discriminates between the class II and class III promoters in vitro as a function of variables that alter the stability of the DNA helix. These variables include ionic strength, temperature, and the presence of denaturing agents such as dimethyl sulfoxide. In general, initiation at the class II promoters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…T7 RNAP uses ATP as the initiating nucleotide at two natural promoters on the T7 genome. The øOL and ø2.5 promoters are, however, rather weak, [14][15][16] observations that are consistent with reduced binding of ATP in the de novo initiation complex. The ternary complexes with T-AA and T-GG showed no density for 3′-dUTP or 3′-dCTP, suggesting that their dissociation constants may be lower than the concentration (5 mM) used for crystallographic studies.…”
Section: Non-consensus Initial Transcribed Sequencementioning
confidence: 75%
“…T7 RNAP uses ATP as the initiating nucleotide at two natural promoters on the T7 genome. The øOL and ø2.5 promoters are, however, rather weak, [14][15][16] observations that are consistent with reduced binding of ATP in the de novo initiation complex. The ternary complexes with T-AA and T-GG showed no density for 3′-dUTP or 3′-dCTP, suggesting that their dissociation constants may be lower than the concentration (5 mM) used for crystallographic studies.…”
Section: Non-consensus Initial Transcribed Sequencementioning
confidence: 75%
“…Thus, the DNA sequence in the extended upstream AT-rich region can play a role in modulating the efficiency of transcription initiation by affecting the affinity of T7 RNAP for the promoter DNA and by affecting the efficiency of promoter clearance. Thus, in addition to the promoter binding region contributing to the differences in promoter strength among class II and between class II and class III promoters, the upstream AT-rich region also appears to be involved in promoter discrimination (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the sequence of this region is variable among the weaker class II promoters, with one or more GC bp interrupting the AT run (14). By observing the salt-regulated transcriptional activity of T7 RNAP in vitro and the usage of promoters in vivo, McAllister and colleagues (15,16) found that shortening this AT-rich region from 9 to 4 bp but keeping the integrity within the Ϫ13 to Ϫ17 region was sufficient to make a class III promoter act more like a weaker class II promoter. Promoter 3.8 is the only class II promoter with uninterrupted AT runs from Ϫ13 to Ϫ22, and it behaves more like a class III promoter (14,15).…”
mentioning
confidence: 99%
“…Within the seminiferous tubules, the physical organization of the germ cells reflects the extent of differentiation, so that the least mature stem cells are located furthest outside, and the most mature spermatazoa are located inside the lumen (15,16). To determine which cell types in the testis express HSP86, the distribution of HSP86 mRNA was analyzed by in situ hybridization (20) with antisense and control sense RNAs transcribed in vitro (8,13). The antisense HSP86 RNA hybridized in a ringlike pattern to the outside portion of the seminiferous tubules, corresponding to the distribution of immature spermatogenic cells (Fig.…”
mentioning
confidence: 99%